EFFECT OF DOSAGE AND LENGTH OF INCUBATION DUCK MANURE ON GROWTH AND YIELD OF PURPLE EGGPLANT ON ALLUVIAL SOIL - Korintus Putra; Basuni Basuni; Darussalam Darussalam (Jurnal Sains Pertanian Equator, 2022)
ABSTRACKEggplant is a vegetable plant that has prospects for cultivation and can alsogrow on various types of soil, one of which is alluvial soil. Utilization of alluvial soilfor purple eggplant cultivation is faced with various obstacles. Efforts can be made toimprove the level of soil acidity by liming, while to improve the physical andchemical properties of the soil was to apply duck manure. This study aims were todetermine the dose and length of incubation of duck manure that provides the bestgrowth and yield of purple eggplant grown in alluvial soil. This research wasconducted at Jl. Purnama 2 Pontianak City from March 18th to June 4th 2021. Thisstudy used a Complete Randomized Design (CRD) with two factors threerepications. The first factor was the dose of duck manure fertilizer (B), consisting of4 levels, namely 300, 450, 600, and 750 g / polybag equivalent to 10, 15, 20, and 25tons / ha. The second factor was the length of incubation (I), consisting of 3 levels, 1,2, and 3 weeks of incubation. Variables observed were plant height, root volume,plant dry weight, number of fruits per plant, weight of fruit, weight of fruit per plant,and diameter of fruit. The results of the study showed that there was no interactioneffect between the dose of duck manure and the length of incubation on allobservation variables. The best dose of duck manure was 750 g / polybag equivalentto gave 25 tons / ha on variable plant dry weight and fruit diameter. Incubationlength of 1 week of duck manure provide the best dry weight of the plant.Keywords: : Alluvial, duck manure, length of incubation, purple eggplant.